2019
DOI: 10.1177/1558925018824901
|View full text |Cite
|
Sign up to set email alerts
|

A review on advanced nanofiber technology for membrane distillation

Abstract: The importance of the nanofiber webs increases rapidly due to their highly porous structure, narrow pore size, and distribution; specific surface area and compatibility with inorganics. Electrospinning has been introduced as one of the most efficient technique for the fabrication of polymeric nanofibers due to its ability to fabricate nanostructures with unique properties such as a high surface area and porosity. The process and the operating parameters affect the nanofiber fabrication and the application of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 115 publications
0
56
0
3
Order By: Relevance
“…The exploitation of new applications of nanofibrous film and its derived nanostructures is undoubtedly one of the hottest topics in the material field over the years [1][2][3][4]. Many breakthrough achievements have been made in applications including tissue engineering, filtration, nano-sensors and nano-electronics, composite reinforcement, energy harvesting and storage, electromagnetic interference shielding, and water treatment [5][6][7][8][9]. For example, Liu et al reported on a high-performance water desalination electrode based on graphene-bonded nanofibers [10].…”
Section: Introductionmentioning
confidence: 99%
“…The exploitation of new applications of nanofibrous film and its derived nanostructures is undoubtedly one of the hottest topics in the material field over the years [1][2][3][4]. Many breakthrough achievements have been made in applications including tissue engineering, filtration, nano-sensors and nano-electronics, composite reinforcement, energy harvesting and storage, electromagnetic interference shielding, and water treatment [5][6][7][8][9]. For example, Liu et al reported on a high-performance water desalination electrode based on graphene-bonded nanofibers [10].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to other treatments, the membrane separation method has higher efficiency, consistent effluent quality, and lower consumption of energy [45]. Based on the separation and pore size type, membranes can be grouped as microfiltration (MF, pore size ranges from 0.1-5 µm), ultrafiltration (UF, pore size ranges of 0.01-0.1 µm), nanofiltration (NF, pore size range of 0.001 to 0.01 µm), and reverse osmosis (RO, pore size range of 0.0001 to 0.001 µm) which are the pressure-driven processes [46,47]. The main types of membrane are classified as follows.…”
Section: Membrane Technologymentioning
confidence: 99%
“…The electrospinning begins from finding a suitable solvent to dissolve the polymer in order to afford sufficient solution viscosity (chain entanglements) and to avoid varicose breakup (to yield droplets) as the electrified jet moves toward the collector. Well-organized and detailed review papers, based on the effect of these parameters, are published in the literature [10,[20][21][22][23][24].…”
Section: Electrospinning Techniquementioning
confidence: 99%
“…The electrospinning begins from finding a suitable solvent to dissolve the polymer in order to afford sufficient solution viscosity (chain entanglements) and to avoid varicose breakup (to yield droplets) as the electrified jet moves toward the collector. Well-organized and detailed review papers, based on the effect of these parameters, are published in the literature [10,[20][21][22][23][24]. Nonetheless, over the past decades, there have been significant advancements and modifications on the conventional laboratory-scale electrospinning technique (single-needle electrospinning), leading to the attainment of a high production rate, desired patterns, and morphologies [20,24].…”
Section: Electrospinning Techniquementioning
confidence: 99%